The Purpose of Crimination Against Perpetrators and Victims in the Perspective of Restorative Justice - Hariyanto Hariyanto; Oksep adhayanto; Fihtriatus Shalihah (Faculty of Law, Universitas Lampung, 2023)
Indonesia implements a punishment system that refers to the absolute theory or theory of retaliation and retributive flow, namely the imposition of punishment is an absolute consequence that must exist as a retaliation to people who have committed crimes so that the basis for justifying the imposition of punishment lies in the existence of the crime itself. Restorative justice is in principle an approach that is used to resolve problems outside the court by mediation or deliberation in achieving justice expected by the parties. The purpose of this study is to provide an overview of the benefits of restorative justice in the criminal law enforcement process. This research is a type of normative legal research. The approach method used is a statutory approach and a conceptual approach. Sources of research data are secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data were analyzed using a qualitative descriptive method. Based on the results of this study, the restorative justice approach is suitable as a punishment goal and is beneficial in reducing the accumulation of cases and the negative stigma of imprisonment. Restorative justice is the settlement of criminal cases involving perpetrators, victims, families of perpetrators/ victims, and other related parties to jointly seek a fair solution by emphasizing restoration to its original state, and not retaliation. Restorative justice is a subsystem of punishment where other subsystems are interconnected and work to achieve benefits. The principle of restorative justice is that victims get compensation for those who suffer losses, peace and agreements that can restore the victim's condition.